2021
DOI: 10.1177/21501327211044888
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Lockdown on Diabetes Complication and Diabetes Management in People With Diabetes in Indonesia

Abstract: Aims: As the country with the seventh largest number of People with Diabetes (PWD) in the world, the Coronavirus disease 2019 (COVID-19) pandemic, and the Large Social Scale Restriction (LSSR) policy taken by the Indonesian government to reduce the number of COVID-19 transmissions is estimated to interfere diabetes management and will increase the incidence of diabetes complications. This study aims to determine the difficulties of diabetes management and its impact on diabetes morbidity during the COVID-19 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The pandemic resulted in fewer number of hospital visits due to the recommendations on social isolation and travel restrictions, loss of the traditional method of communication with the patient, impaired routine diabetic care, and absences of telehealth services. Previous studies have shown that the pandemic resulted in poor glycemic control and increasing incidence of diabetes complications ( Elhenawy and Eltonbary, 2021 ; Kshanti et al, 2021 ; Önmez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic resulted in fewer number of hospital visits due to the recommendations on social isolation and travel restrictions, loss of the traditional method of communication with the patient, impaired routine diabetic care, and absences of telehealth services. Previous studies have shown that the pandemic resulted in poor glycemic control and increasing incidence of diabetes complications ( Elhenawy and Eltonbary, 2021 ; Kshanti et al, 2021 ; Önmez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a participant stated that they use Afrika leaf or Vernonia amygdalina to reduce sugar blood levels. A previous study has found that vernonia amygdalina has little effect on decreasing glucose in diabetic rats (22), but there is still no study on humans. The practice of herbal medicine to treat DM has also been known globally.…”
Section: Avoid Meeting Doctors or Nurses Directly Because They Can Tr...mentioning
confidence: 97%
“…Previous studies stated that people with diabetes in remote areas in India face difficult challenges in self-management during the COVID-19 pandemic (20,21). Another study in Indonesia revealed that people with DM struggle to do self-management during pandemics and also experience psychological distress, but there is still limited qualitative study about the selfmanagement of people with DM in remote areas in eastern Indonesia (22). This study aimed to explore the experience of rural residents with DM in self-management during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties included attending 30.1% of diabetes consultations, 12.4% access to diabetes medication, checking blood glucose levels 9.5%, controlling diet 23.8%, and doing regular exercise 36.5%. Difficulties in managing diabetes during the COVID-19 pandemic are prone to diabetes complications [8].…”
Section: Introductionmentioning
confidence: 99%